Raw Water Supply System Analysis at Randugunting Dam, Blora Regency Province of Central Java - Beni Setiyanto; Bagas Wahyu Adhi (Universitas Islam Sultan Agung, 2022)
Randugunting Dam is one of the government's national strategic projects which has a role in supporting food security. The benefits that will be felt are for flood control, irrigation and raw water. Allocation of raw water 200 lt/sec for three regions, namely Blora Regency 100 lt/sec, Pati Regency 50 lt/sec and Rembang Regency 50 lt/sec. The purpose of this study is to provide an analysis of the hydraulic design of the piping system to each WTP and water quality. The system used is the intake of raw water from the dam intake distributed to a centralized WTP then to the District WTP. The first analysis obtained the results of intake to a centralized WTP using PE pipe 400mm the average HGL value is 78.75m higher than the average elevation hs 68.79m, 9.97m residue, final pressure 0.128bar; the second condition is centered on the Blora IPA using PE pipe 350mm plus a pump capacity of 100 lt/s the average HGL value is 202.17m higher than the average elevation hs 114.94m, residue 87.23m, final pressure 0.977bar; The evaluation of the pollution index against the class II water quality standard in the three samples is classified as good water condition